Confinement effect and efficient adsorption of furfural onto ZIF‐8‐derived microporous carbon. Issue 5 (15th February 2023) - Yuan, Min; Liu, Zhiqing; Lv, Tiantian; Dong, Jinxiang; Shi, Qi
Abstract: BACKGROUND: The separation of furfural from a low‐concentration multicomponent and acid‐containing aqueous solution is a highly demanding process; traditional distillation requires an excessive amount of energy. Herein, we demonstrated ZIF‐8‐derived microporous carbon (C) as a promising adsorbent for the separation of furfural using adsorption isotherms, dynamic column adsorption, adsorption kinetics and desorption studies. RESULTS: In the competitive adsorption kinetics experiments with a furfural/acetic acid concentration of 50/20 g L −1, the acetic acid adsorbed in the micropores of NCZIF‐8 1000C‐800A gradually was replaced by furfural, whereas the amount of acetic acid in the mesopores of NCZIF‐8 800C‐800A slowly increased. In addition, the micropores of NCZIF‐8 1000C‐800A exhibited highly efficient and fast adsorption characteristics toward furfural over a wide furfural/acetic acid concentration range (0–50/0–20 g L −1 ) with the furfural adsorption capacity reaching an adsorption equilibrium within 10 min. The results show that the high Brunauer–Emmett–Teller surface area of NCZIF‐8 1000C‐800A is responsible for the high furfural adsorption capacity (1205.3 mg g −1 ) and the confined microporous structure can strengthen the π–π interactions between porous C and furfural, thereby enhancing the selectivity of furfural/acetic acid (61.4) in the furfural/acetic acid (50/20 g L −1 ) dynamic column adsorption system. Meanwhile, the desorption ratio of furfural in the dynamic desorption system reached as high as 98.6%. CONCLUSION: The unique micropore‐confinement effect and excellent adsorption behavior make NCZIF‐8 1000C‐800A an efficient adsorbent for furfural in the furfural–acetic acid system. © 2023 Society of Chemical Industry (SCI).